Toxic epidermal necrolysis with good response to methylprednisolone pulses - Vílchez-Rivera, Stalin (2020)
A 15-year-old woman, who, after receiving lamotrigine by uncontrolled epilepsy, developed generalized erythema, blisters and flaking, with mucous membrane involvement and covering 60%-80% of the body surface area.The clinical picture of toxic epidermal necrolysis was confirmed by skin biopsy. In addition to support measures, she was given methylprednisolone pulses with rapid favorable response.